Analisis Faktor-Faktor yang Mempengaruhi Keterlambatan Laporan Audit - Robby Krisyadi; Noviyanti Noviyanti (Politeknik Ganesha Medan, 2022)
This study aims to determine the factors that affect delay of audit report. The population of research are companies listed in Indonesia Stock Exchange in 2016 – 2020. The sampling technique used purposive sampling method with 1870 annual report processed. The data analysis technique of this research uses multiple regression and assisted by SPSS software and Eviews software. The result of this research showed that audit opinion and profitability is significantly negative to audit delay, and firm size is significantly positive to audit delay, whereas audit effort, public accounting firm size, debt and ownership concentration have no effect to audit delay. The results of this study are expected to contribute to strengthening agency theory in safeguarding the interests of agents and principals by submitting financial statements in a transparent and timely manner to prevent information asymmetry, as well as strengthening signal theory in explaining the factors for the spread of good news and bad news of companies to investors. In addition, practical contributions for company management can be used as a source of information to find solutions to improve the timeliness of submitting financial reports, for auditors it is expected to be a guide in preparing audit procedures that are more effective in overcoming factors that cause delays in audit reports, and for service authorities. The financial statements are expected to be the basis for policies to strengthen supervision of companies listed on the IDX in submitting annual reports in a timely manner.